Jack mezirow's transformative learning on the dimension of critical thinking and digital literacy: a needs analysis study - Saputro, Johan Dwi (Jurnal Pendidikan PKN (Pancasila dan Kewarganegaraan), 2025)
This research aims to analyze the need for a transformative learning model design based on Jack Mezirow's theory to enhance critical thinking skills and digital literacy. The approach used in the research is descriptive qualitative using surveys. Data were obtained from interviews with three teachers and questions in the form of questionnaires directed at 45 eleventh-grade students in Ponorogo Regency. The research results obtained indicate that the dominant type of learning is conventional learning, which has not yet maximally encouraged critical reflection and active student participation. Most teachers do not fully understand transformative learning, although they are aware of some potential aspects and the relevance of open learning, discussions, self-reflection, and the development of logical argumentation. Based on these results, it can be concluded that there is an urgency to design a learning model that is contextual and adaptive, capable of fostering critical, reflective, and digitally literate character in students as a form of readiness to face the challenges of the 21st century